If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-12x=6(1-x)
We move all terms to the left:
8-12x-(6(1-x))=0
We add all the numbers together, and all the variables
-12x-(6(-1x+1))+8=0
We calculate terms in parentheses: -(6(-1x+1)), so:We get rid of parentheses
6(-1x+1)
We multiply parentheses
-6x+6
Back to the equation:
-(-6x+6)
-12x+6x-6+8=0
We add all the numbers together, and all the variables
-6x+2=0
We move all terms containing x to the left, all other terms to the right
-6x=-2
x=-2/-6
x=1/3
| -4=80-30x | | 174=5x+7(5x+2) | | 8+12x=6(1+x) | | (x+7)(x-7)=12 | | 0.35x1.5=0.525 | | 8+12x=6(1=x) | | 8x+40=90-2x | | 1/3x+6=3/4(x+8) | | -112=7x | | 90=-3(3v-6) | | 6x-16=2x+8 | | 3/2(x-8)=1/4x+3 | | 4/5k-1/10k=1/2k+1 | | 1/8x+3=5 | | -105=7(6-7x) | | 2/5(x+5)=1/5(x+4) | | 8*m=96÷3 | | -8x+26=12x-14 | | 5x-46=-96 | | 2n^2+13n-57=0 | | w=0.0026(83)(666)√3/4.3 | | 7(p-8)=-84 | | 1-6/(2x-5)=0 | | y^2+12y=620 | | -46=4x+14 | | 7(p-80=-84 | | -14x-10=10x+2 | | 6x^2-62x+112=0 | | b/4+8=9 | | 16x+54=4x-6 | | 4(2a+3=3(3a-4) | | 4a÷2a=54-a |